A Structure and Durability Comparison of Membrane Electrode Assembly Fabrication Methods: Self-Assembled Versus Hot-Pressed. Issue 6 (21st February 2018) - Hack, Jennifer; Heenan, T. M. M.; Iacoviello, F.; Mansor, N.; Meyer, Q.; Shearing, P.; Brandon, N.; Brett, D. J. L.
Abstract : The most common means of fabricating membrane electrode assemblies (MEAs) for polymer electrolyte fuel cells (PEFCs) involves a hot-press step. The conditions used to perform the hot-press impacts the performance and durability of the fuel cell. However, the hot-press process is not essential for achieving operational MEAs and some practitioners dispense with the hot-press stage altogether by using a self-assembled approach. By performing the integration of the components in-situ during fuel cell assembly, there is the potential to lower the cost and time of manufacture. This study investigates the electrochemical performance and mechanical microstructure of MEAs that were either hot-pressed or self-assembled (non-hot-pressed) and compared at beginning-of-test (BOT) and end-of-test (EOT), following accelerated stress testing. Hot-pressed and self-assembled MEAs were found to show negligible difference in their performance and almost identical performance degradation. X-ray computed tomography (X-ray CT) showed distinct differences in the microstructure of the electrodes. In addition to a crack network in the catalyst layer, the self-assembled samples exhibit indentations that were not present in the hot-pressed sample. It was concluded that in-situ assembly of MEAs could be a suitable means of fabricating PEFC MEAs.